1991
DOI: 10.1017/s0950268800048779
|View full text |Cite
|
Sign up to set email alerts
|

Antigens recognized by the human immune response to severe leptospirosis in Barbados

Abstract: SUMMARYSerum samples obtained from patients hospitalized in Barbados with severe leptospirosis were tested by the microscopic agglutination test (MAT), enzyme immunoassay (EIA) and immunoblotting with leptospires that had been isolated from these patients. While serum samples taken a few days after onset of symptoms often showed no apparent correlation between MAT and EIA, later sequential serum samples produced similar profiles in both tests during the course of infection. Immunoblotting sonicate from Leptosp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
15
0
5

Year Published

1994
1994
2017
2017

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 29 publications
(36 reference statements)
5
15
0
5
Order By: Relevance
“…It has been reported that 7 days after the onset of clinical symptoms in human patients, 62% had anti-LigB IgG antibodies as detected by WB analysis (13). Similar results with IgG antibody responses to other leptospiral recombinant proteins have also been reported (12,(36)(37)(38). This suggests that these horses were previously infected with Leptospira and developed a memory response upon re-exposure to Leptospira.…”
Section: Discussionsupporting
confidence: 72%
“…It has been reported that 7 days after the onset of clinical symptoms in human patients, 62% had anti-LigB IgG antibodies as detected by WB analysis (13). Similar results with IgG antibody responses to other leptospiral recombinant proteins have also been reported (12,(36)(37)(38). This suggests that these horses were previously infected with Leptospira and developed a memory response upon re-exposure to Leptospira.…”
Section: Discussionsupporting
confidence: 72%
“…Among sera from patients presenting with less than 7 days of symptoms, 62% had anti-rLigB IgG antibodies as detected by the immunoblot assay. Similar findings have been observed with IgG antibody responses to other Leptospira proteins (10,11,20,22). This may relate in part to a memory response in individuals with a prior exposure to leptospirosis.…”
Section: Vol 45 2007 Leptospira Ig-like Proteins In Leptospirosis Psupporting
confidence: 81%
“…3). With respect to the IgG response, the LipL32 C terminus was recognized by antibodies present in the sera of five patients during the acute phase of the disease, and the intermediate subfrag- (4,5,9,10,19,21). Our data indicate that LipL32 can be used as a diagnostic antigen for the acute and convalescent phases of patients with leptospirosis.…”
Section: Discussionmentioning
confidence: 78%